Complement C1q and von Willebrand factor interaction in atherosclerosis of human carotid artery - Schulz, Kristina; Donat, Claudia; Punjabi, Mukesh; Glatz, Katharina; Kaufmann, Beat; Trendelenburg, Marten (Frontiers in Immunology, 2023)
Atherosclerosis is an inflammatory disease of the vessel wall with cholesterol crystal (CC) deposition being a hallmark of the disease. As evidence for a cross-talk between complement activation and hemostasis on CC surfaces has been limited to in vitro data, the aim of this study was to demonstrate the presence of C1q-vWF complexes in human atherosclerosis ex vivo. We used immunofluorescence staining and proximity ligation assay (PLA, Duolink®) to examine the presence, localization and co-localization of C1q and vWF in frozen sections of human carotid arteries with atherosclerosis or without atherosclerotic changes as well as material from thrombendarteriectomy. We observed significantly higher levels of C1q and vWF in healthy tissue compared to diseased material as well as a greater co-localization in the PLA in healthy samples than in diseased samples. In diseased samples, fluorescence signals were highest in locations encompassing atheroma and foam cells. While there was overall reduced signal in areas with CC, the staining was spotty and there was evidence for co-localization on individual CC. Thus, we demonstrate the presence of C1q-vWF complexes in human carotid arteries ex vivo, which is most abundant in healthy endothelial and subendothelial space and reduced in diseased tissue. C1q-vWF interaction can also be demonstrated on CC surface.